MO882PATIENTS' UNDERSTANDING AND EXPERIENCE OF COVID-19 PANDEMIC AMONGST IN-CENTRE HAEMODIALYSIS POPULATION IN A SINGLE UK CENTRE. (29th May 2021) - Ng, Khai Ping; Crowley, Lisa; Aggarwal, Yogita; Baharani, Jyoti
Abstract: Background and Aims: Patients with end-stage kidney disease on dialysis are susceptible to severe COVID-19 infections. However, during the pandemic, many renal patients were unable to 'shield' fully due to the ongoing need to attend the dialysis unit for treatment. With a significant proportion of our haemodialysis population coming from socially deprived and ethnic minority background (38%), we aimed to explore patients' understanding and experience of COVID-19 pandemic. Method: This was a cross-sectional survey of patients receiving in-centre haemodialysis from one centre in England conducted during July 2020, three months after the first UK national lockdown. The questionnaire consisted of 18 questions exploring patients' awareness of COVID-19 pandemic, understanding of 'shielding', use of face covering, and their experience of haemodialysis treatment as well as accessing healthcare during COVID-19 pandemic. Those with language barriers were offered assistance and verbal translation by haemodialysis nurses, if possible, to complete the questionnaire. Results: In total, 232 patients (of a total of 479 in-centre dialysis patients, 48% response rate) completed and returned the questionnaire. Of these, 29 (12.5%) patients required help with the questionnaire due to language barrier. Mean age was 62 (SD 16) years, 63% were male, 53% were from ethnic minorities and 45% were from the most deprived area (MDI Decile 1). A third of the respondents lived with 3 or more adults at home and a quarter lived with one or more child. Majority of the patients (97%) were aware of COVID-19 pandemic, and most received information on COVID-19 from the news (87%). Dialysis staff (43.1%), family and friends (32.6%), internet (31%) and general practitioners (20.3%) were also key sources of information. Despite this, 17.2% of the patients did not know about 'shielding'. Even though 3 in 4 patients stated that they were 'always' or 'often' able to 'shield', when prompted with scenarios, significant number of patients in fact felt that they were unable to shield when travelling to dialysis (56%), during dialysis (35%) or when shopping (17%). Majority of the patients (89%) said that they wore face covering and 28% self-isolated from the rest of household during the first peak of pandemic. 83% practised 'social distancing' at dialysis units but 5% did not and 6% felt unable to do so. Almost a quarter of the patients (23%, 54 patients) felt unwell during the first wave of COVID-19. Majority (50%) of them sought medical help by informing the dialysis unit, whilst 26% contacted their GP and 38% attended emergency departments. Of these 54 patients, 35% had difficulties accessing medical help, especially from primary care. One in four patients felt that their dialysis experience had changed during the pandemic: 10% increased use of private taxis or used different travel services, 3.5% reported increased travel time, 8% dialysed at a different unit, 5% experienced longer waiting time to start dialysis sessions and 4% had dialysis frequency reduced . Almost a third (29%) of the patients knew of someone in the dialysis unit who had COVID-19 infection during the first wave of pandemic. Conclusion: COVID-19 posed significant challenges for patients receiving in-centre haemodialysis. Despite their high susceptibility to severe COVID infection, significant number of patients was not aware of 'shielding' or able to 'shield' effectively. Some also experienced difficulties accessing medical help and a quarter reported change of transport or dialysis arrangement during the pandemic.